What is The Association between Family-Centered Care Models in Medical Rehabilitation and Improved Family Well-Being and Child Outcomes? : A Systematic Review - Putri Fajaria Anggraini (The International Journal of Medical Science and Health Research, 2026)
Background: Family-centered care (FCC) is increasingly recognized as a fundamental approach in pediatric rehabilitation, yet the strength and consistency of its association with improved family well-being and child outcomes across diverse medical rehabilitation settings require systematic synthesis. Methods: This review synthesized evidence from 80 RCT, etc examining FCC interventions in pediatric medical rehabilitation. Settings included neonatal intensive care units (NICUs), inpatient rehabilitation, outpatient clinics, home-based programs, and community-based early intervention. Results: FCC demonstrated significant positive associations with child outcomes across multiple populations. In preterm infants, meta-analyses showed FCC significantly improved breastfeeding rates (OR=5.92, 95%CI:2.37-14.82, P<0.001), weight gain (MD=3.16 g/day, 95%CI:2.51-3.80, P<0.001), and reduced one-month readmission (OR=0.37, 95%CI:0.22-0.61, P<0.001)(1,2). In children with cerebral palsy, community-based family-child-centered care produced superior gross motor function (GMFM-66), balance, and quality of life compared to conventional rehabilitation (P<0.05)(4). For family well-being, FCC significantly reduced parental stress (SMD=-0.19 to -0.20, P<0.001), anxiety (SMD=-0.19, P<0.001), and depression (SMD=-0.37, P=0.004)(2). Parent satisfaction showed dramatic improvement (OR=11.20, 95%CI:4.76-26.34, P<0.001)(2). Family empowerment significantly improved (mean change +4.1 points, 95%CI:3.3-4.9, P<0.001)(12). Biological validation was demonstrated through reduced maternal hair cortisol at 18 months (B=-0.22, 95%CI:-0.41,-0.04)(44). Discussion: FCC effects are most robust in NICUs where parents serve as direct intervention agents. Effect magnitudes vary by outcome domain, with strongest evidence for parental stress reduction, satisfaction, and neonatal clinical indicators. Child motor outcomes show modest but statistically significant improvements. Family engagement intensity functions as a dose-response moderator. Conclusion: FCC is significantly and positively associated with improved child outcomes and family well-being across pediatric medical rehabilitation settings. Implementation should prioritize structured information sharing and professional training to optimize effectiveness.